Peran Jaringan Sosial dalam Kewirausahaan di Banjarmasin: Tinjauan Sistematis terhadap Keterhubungan dan Dampaknya terhadap Kesuksesan Bisnis - Muhammad Fernanda Rizaldy; Hastin Umi Anisah; Mahdi Hidayatullah (Jurnal Bintang Manajemen, 2024)
This study presents a systematic literature review (SLR) to explore the role of social networks in entrepreneurship within the context of Banjarmasin. The research investigates how social connections affect business success, focusing on the influence of networking in developing sustainable ventures. By analyzing peer-reviewed articles published over the last decade, the study identifies key themes, including community support, collaboration, network strength, and access to resources, which act as significant drivers for business growth. Both formal and informal networks are found to play essential roles in enhancing entrepreneurial outcomes. The findings suggest that optimizing these social networks is crucial for achieving sustainable business development. This study offers practical insights for entrepreneurs and policymakers, aiming to provide strategies that leverage local social capital for improved business performance in Banjarmasin.